Analisis Faktor Yang Mempengaruhi Perilaku Konsumen Pada Pengguna Iphone Di Kota Samarinda Ditinjau Dari Sudut Pandang Konsumsi Monzer Kahf - Tika Parlina; Dharma Yanti (Borneo Islamic Finance and Economics Journal, 2021)
The study aimed to analyze the factors that consumer behavior illustrates by Brand Image, Brand Awareness, and Perceived Quality toward brand loyalty and iPhone brand phone repurchase intention. This study was conducted on iPhone brand mobile phone users in Samarinda City with a sample of 125 respondents. To obtain research data used instruments in the form of questionnaires with a scale likert 5. For data testing used Smart PLS (Partial Least Square). After looking at the factors that influence consumer behavior, an analysis of the consumption point of view according to the concept of an Islamic economic figure, Monzer Kahf, associates rationalism, the concept of goods in Islam, and consumer norms / ethics. The results of this study are that brand image variables and brand awareness and perceive quality can explain the formation of brand loyalty with R2 of 0.768 and the second variable of brand image and brand awareness and perceived quality coupled with brand loyalty can explain the formation of repurchase intention with R2 of 0.721. For influence between variables, it shows that the stronger the brand image and brand awareness and the perceived quality on the iPhone brand phone, the higher the brand loyalty and also repurchase intention in iPhone brand phones. However, in contrast, two of these variables, namely brand awareness and perceived quality, negatively and insignificantly affect the interest in buying iPhone phones in Samarinda City. As well as in Kahf's point of view on the factors that influence the behavior of iPhone users in Samarinda City no ethics and morals are violated or still in accordance with the concept as consumers in the world.